A review of stroke order in Hanzi handwriting - Zhang, Haiwei (Language Learning in Higher Education, 2014)
This article reviews the current research on stroke order of hanzi (as used to write the Chinese, Japanese and Korean languages) in teaching Chinese as a second language (CSL). Based on an extensive review of current research on stroke order, it first discusses the importance and difficulty of stroke order in hanzi learning. It goes on to present the mixed attitudes held by CSL learners and teachers towards learning stroke order, followed by a synthesis of the literature on stroke order errors and current methods of displaying and practising stroke order. Finally, some key implications for teaching and learning stroke order are suggested, and future research directions are proposed for the Chinese language classroom.